2020
DOI: 10.1080/0886022x.2020.1729188
|View full text |Cite
|
Sign up to set email alerts
|

PPAR γ/TLR4/TGF-β1 axis mediates the protection effect of erythropoietin on cyclosporin A-induced chronic nephropathy in rat

Abstract: PPAR γ/TLR4/TGF-β1 axis mediates the protection effect of erythropoietin on cyclosporin A-induced chronic nephropathy in rat Bin Liu & Ping Tan To cite this article: Bin Liu & Ping Tan (2020) PPAR γ/TLR4/TGF-β1 axis mediates the protection effect of erythropoietin on cyclosporin A-induced chronic nephropathy in rat,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…As our results unveiled, the contents of SCr, BUN, and mALB were clearly elevated after silencing of PPARc. In line with this finding, when PPARc is inhibited, serum levels of SCr and BUN are elevated, and renal function is damaged in rats with chronic nephropathy [29]. In the present study, there was obvious renal interstitial fibrosis in the renal tissue of HN rats, while the degree of renal interstitial fibrosis was clearly aggravated by silencing of PPARc.…”
Section: Discussionsupporting
confidence: 87%
“…As our results unveiled, the contents of SCr, BUN, and mALB were clearly elevated after silencing of PPARc. In line with this finding, when PPARc is inhibited, serum levels of SCr and BUN are elevated, and renal function is damaged in rats with chronic nephropathy [29]. In the present study, there was obvious renal interstitial fibrosis in the renal tissue of HN rats, while the degree of renal interstitial fibrosis was clearly aggravated by silencing of PPARc.…”
Section: Discussionsupporting
confidence: 87%
“…There was degeneration with exfoliation of some cells inside the lumen in the D.C.T and the peritubular capillaries were congested and extravasated. Liu and Tan (2020) reported that in cyclosporin A treated group there was marked vacuolar degeneration, atrophy, necrosis and exfoliation of kidney tubules, interstitial fibrosis, glomerular atrophy, and vascular congestion. Also, Al-Sa'aidi et al (2019) found that cyclosporine caused obvious atrophy of glomeruli, necrosis of Bowman capsule lining, cystic dilation of renal convoluted tubules and necrosis of their lining.…”
Section: Discussionmentioning
confidence: 98%
“…(4) Ombuin + T0070907 group ( n = 10), in which rats were received 1 mg/kg/day T0070907 intraperitoneally based on the treatment of Ombuin group. The doses of T0070907 used in the current experiments were determined previously (Liu & Tan, 2020). (5) T0070907 group ( n = 10), in which rats were intraperitoneally injected with 1 mg/kg/day T0070907.…”
Section: Methodsmentioning
confidence: 99%